The relationship of physical work efficiency (PWC 170) with enduring attacking skilled-performance and shooting accuracy of Premier League club handball players for the season 2018-2019 - Kadhim, Mohammed Mahmood; HAMDAN, RAAD KHANJAR (International Journal of Psychosocial Rehabilitation, 2020)
The intentional research sample consisted of students formally registered within the Iraqi Central Handball Federation for the sports season (2018-2019) . And their number reached (14) players who did not represent the players of Baghdad governorate with handball. The two researchers used the descriptive approach (the study of correlational relations) for its relevance and the nature of the research. As this approach is one of the best and most appropriate approaches to solving the current research problem and achieving its objectives. The physical work efficiency test at the pulse was used (170 Capacity physical Working) to detect the level of efficiency of the productivity of the circulatory and respiratory system, blood and muscle efficiency on the oxygen consumption and energy production of players. The researchers used tests (long handling and accurate steering ball from a distance (30) M and test ran distance (30 meters) "with handling ball ended thoroughly test meters with handling ball ended accurately ran distance (107) and the test ran a distance (130) meters (ending with accuracy of correction) to detect and identify the level of attacking skill performance and accuracy of correction of the players.